Ordböcker och informationsbeteende En gränsöverskridande studie i ordboksanvändning - Granström, Alexandra (Nordiske Studier i Leksikografi, 2007)
Dictionaries and information behaviour – a cross boundary study in dictionary use.User studies is a dynamic and well developed field in Library and Information Science (LIS). The research deals principally with the phenomena of information behaviour especially concerning information needs, information seeking and information use. This article examines the relation between user studies in LIS and in lexicography by analysing the common user aspects need, seeking and use. A study in dictionary use among librarians forms the empirical foundation for a theoretical discussion about the information behaviour process in relation to dictionary use. The interdisciplinary approach gives a deeper understanding of the dictionary user as an actor in a complex user context. User studies in LIS is an inspiring field for further studies in dictionary use also among other user groups.